2014
DOI: 10.1007/s11845-014-1099-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of transcricoid lignocaine as adjunctive local anaesthesia for fiberoptic bronchoscopy

Abstract: The findings of the study demonstrate that the use of transcricoid injection of lignocaine provided a safe adjunct for anaesthesia in flexible bronchoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Drug administration via cricothyroid injection also found better VAS scores for ease of procedure and cough than spray-as-you go technique in sedation bronchoscopy. [160] Other studies have also reported similar results with cricothyroid injection, demonstrating faster procedure times[161] and better quality of anesthesia. [162] In a recent RCT, cricothyroid injection demonstrated superiority over the spray technique.…”
Section: Premedicationmentioning
confidence: 76%
“…Drug administration via cricothyroid injection also found better VAS scores for ease of procedure and cough than spray-as-you go technique in sedation bronchoscopy. [160] Other studies have also reported similar results with cricothyroid injection, demonstrating faster procedure times[161] and better quality of anesthesia. [162] In a recent RCT, cricothyroid injection demonstrated superiority over the spray technique.…”
Section: Premedicationmentioning
confidence: 76%
“…Dyclonine hydrochloride mucilage is a local anesthetic with strong penetration and a lasting effect. It enhances the ease of the procedure and cough suppression in patients undergoing flexible bronchoscopy and serves as an important and underutilized adjunct to local anesthesia in flexible bronchoscopy . Dyclonine hydrochloride mucilage is used for anesthesia and lubrication of the larynx before a bronchoscope examination.…”
Section: Discussionmentioning
confidence: 99%
“…Following criteria were set for the evaluation of anesthesia. 6 Excellent anesthetic effect: smooth bronchoscopy operation, patients remaining silent during microscopic examination, occasional slight cough, no nausea and retching; good anesthetic effect: smooth bronchoscopy operation, mild cough during microscopic examination, cough less than six times, occasional nausea and retching; medium anesthetic effect: smooth bronchoscopy operation, continuous cough during microscopic examination, mild nausea and retching; and poor anesthetic effect: no smooth bronchoscopy operation, restless patient, violent cough lasting for a long time during microscopic examination, symptoms of nausea and frequent retching, hard breath or hypoxia cyanosis for long time.…”
Section: Methodsmentioning
confidence: 99%